Evaluation of Hydrochemical and Microbiological Contaminants isolated from Brass River in Niger-Delta Ecological Zone - Thomas Ohwofasa, Ikpesu; Adenike Bosede, Ariyo (Journal of Science and Technology, 2017)
Abstract: The health status of Brass River, a major Rivers in fragile Niger-Delta ecological was investigated. The total viable bacterial counts and hydro-chemical characteristics were measured using internationally approved methods for the assessment of water. The total viable bacterial counts observed were; total heterotrophic bacteria (2.1 Ã— 104) cfu/ml, total coliform count (13 MPN/100 ml) and total feacal coliform (8 MPN/100 ml). The species isolated from the Rivers are Bacillus species, Staphylococcus aureus, Pseudomonas species, Escherichia coli, Enterobacteria species, Salmonella species and Shigellas species. The high viable bacteria count was an indication of the contamination of the river, and the observed hydro-chemical values exceeded the permissible limits set by Nigeria Environment Standards Regulation Enforcement Agency (NESREA). This call for sensitization and regular monitoring of the Niger-Delta aquatic environment in order to reduce the hazardous effects on people in this region that rely on the water from the rivers for home usages. Possibility of outbreak of epidemic is envisaged, if drastic steps are not taken.Keywords: Waste water, Bacillus species, Hydro-chemical parameter, Niger-Delta, Salmonella species